2017
DOI: 10.1097/bot.0000000000000962
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Vacuum Phenomenon Related Intra-articular or Subfascial Gas Found on Computer-Assisted Tomography (CT) Scans of Closed Lower Extremity Fractures

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…For example, in the traumatic setting, a closed fracture creates a negative pressure gradient that pulls dissolved gas out of the tissue, leading to gaseous accumulation in closed intra-articular fractures. 24 Noble et al 24 found that this “vacuum phenomenon” accounted for the presence of intra-articular gas seen on CT in 20% of closed intra-articular fractures in their series.…”
Section: Discussionmentioning
confidence: 96%
“…For example, in the traumatic setting, a closed fracture creates a negative pressure gradient that pulls dissolved gas out of the tissue, leading to gaseous accumulation in closed intra-articular fractures. 24 Noble et al 24 found that this “vacuum phenomenon” accounted for the presence of intra-articular gas seen on CT in 20% of closed intra-articular fractures in their series.…”
Section: Discussionmentioning
confidence: 96%
“…14 This phenomenon has also been described in the setting of closed lower extremity fractures. 15 We attempted to negate this as a potential confounder in our study by obtaining CT scans prior to creation of each arthrotomy. One must be careful to assume the vacuum phenomenon is a false positive in the setting of a periarticular wound.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Noble et al reported that they found gas in as many as 23.5% (27 of 88) of closed tibial fractures using CT scans. 4 The authors speculated that the acute joint dislocation or a closed fracture produces negative pressure where dissolved gas from the solution results in gas accumulation, which is known as the vacuum phenomenon. In the present study, 3 of the 45 closed shaft fractures showed air in the leg.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that the presence of air in the leg was not rare on a computed tomography (CT) scan, even in closed lower extremity fractures. 4 Thus, there remains controversy whether air in the leg is representative of contamination.…”
Section: Introductionmentioning
confidence: 99%